2022
DOI: 10.1063/5.0099164
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent swift heavy ion induced Au nanoparticle elongation in SiO2 matrix

Abstract: The elongation of spherical Au nanoparticles embedded in [Formula: see text] under swift heavy ion (SHI) irradiation is an extensively studied phenomenon. The use of a TEM grid as a substrate facilitates the identification of the same nanoparticle before and after the irradiation. Since the underdensification of [Formula: see text] inside the ion track plays a key role, the elongation is sensitive to the matrix material properties. Therefore, we studied the elongation process of SHI irradiated Au spherical nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The thermal spike nature has been proposed to interpret different crystallographic orientations of materials; see for example reference [56]. Ion irradiation of amorphous SiO 2 in various energy ranges (between 1 MeV and 1 GeV) causes structural changes [43]. It is demonstrated that high-energy ions cause the formation of track structures in silica above a threshold of electronic energy loss of 1.4 keV nm −1 , depending on the specific energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal spike nature has been proposed to interpret different crystallographic orientations of materials; see for example reference [56]. Ion irradiation of amorphous SiO 2 in various energy ranges (between 1 MeV and 1 GeV) causes structural changes [43]. It is demonstrated that high-energy ions cause the formation of track structures in silica above a threshold of electronic energy loss of 1.4 keV nm −1 , depending on the specific energy.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that different morphologies can be obtained based on the size of the initial sample by researchers at CNRS in Caen, France [35]. Precision aligned nanorods can be easily fabricated using swift heavy ion beam irradiation [36][37][38][39][40][41][42][43][44]. An investigation by the author and coworkers [45] examined the relationship between metal particle size and deposited energy.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen from Inmatec PN 1150 nitrogen generator (99.999% purity) was used as a carrier gas as well as for purging between the precursor pulses. For the deposition of SiO 2 , 32,36 (3-aminopropyl)-triethoxysilane (APTES) (Sigma Aldrich, 99%), deionized water, and O 3 were used as precursors. The growth of 50 nm SiO 2 corresponded to 1250 cycles (36 h).…”
Section: Methodsmentioning
confidence: 99%
“…In order to embed the nanorods inside SiO 2 , another 50 nm of SiO 2 was deposited by ALD. 32 The fabrication of Au nanorods was made as following: a thin layer of gold (15-20 nm thickness) was rst deposited using Ultra High Vacuum (UHV) evaporator. The next step was the milling of a selected area by 30 keV Ne + beam in HIM.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation